1 V bias 67 GHz bandwidth Si-contacted germanium waveguide p-i-n photodetector for optical links at 56 Gbps and beyond - Chen, H.; Verheyen, P.; De Heyn, P.; Lepage, G.; De Coster, J.; Balakrishnan, S.; Absil, P.; Yao, W.; Shen, L.; Roelkens, G.; Van Campenhout, J. (Optics express, 2016)
We demonstrate a 67 GHz bandwidth silicon-contacted germanium waveguide p-i-n photodetector operating at -1 V with 6.8 fF capacitance. The dark current is below 4 nA. The responsivity is 0.74 A/W at 1550 nm and 0.93 A/W at 1310 nm wavelength. 56 Gbps on-off-keying data reception is demonstrated with clear open eye diagrams in both the C-band and O-band.